2018
DOI: 10.1021/jacs.8b03895
|View full text |Cite
|
Sign up to set email alerts
|

Many Body Effects and Icosahedral Order in Superlattice Self-Assembly

Abstract: We elucidate how nanocrystals "bond" to form ordered structures. For that purpose we consider nanocrystal configurations consisting of regular polygons and polyhedra, which are the motifs that constitute single component and binary nanocrystal superlattices, and simulate them using united atom models. We compute the free energy and quantify many body effects, i.e., those that cannot be accounted for by pair potential (two-body) interactions, further showing that they arise from coalescing vortices of capping l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 43 publications
7
64
0
Order By: Relevance
“…9c), that converges to the dry equilibrium separation reported in Ref. 39. Rather interestingly, as shown in Fig.…”
Section: Self-assembly Of Ncssupporting
confidence: 87%
See 1 more Smart Citation
“…9c), that converges to the dry equilibrium separation reported in Ref. 39. Rather interestingly, as shown in Fig.…”
Section: Self-assembly Of Ncssupporting
confidence: 87%
“…Following our previous simulations [37][38][39] we kept the temperature at T = 387 K, where according to ref. 34, the toluene coexistence between liquid and gas occurs at a pressure P c (387 K) = 1.097 atm, saturated densities ρ l = 777.9 kg m −3 and ρ g = 3.3 kg m −3 , and isothermal compressibility κ T = 1.866 × 10 -4 atm −1 .…”
Section: Pure Toluenementioning
confidence: 99%
“…Nevertheless, we found that the, ostensibly, nonbonded platelet systems we studied exhibit a form of bonding that could be extracted from considering effective interactions arising between platelets. We consider the form of bonding discussed here different not only from chemical bonds but also from nonbonded interactions considered in, e.g., proteins and clusters (37,(45)(46)(47)(48)(49)(50)(51). There, supramolecular objects reconfigure among different conformations via transition states that can also be described with disconnectivity graphs.…”
Section: Discussionmentioning
confidence: 99%
“…To leverage this topological order in experiment we note that though our order parameters are based on contact types that nominally arise at infinite pressure, we showed that topological order persists at finite pressure. This finding is potentially useful in constructing plasmonic materials that have robust response in the presence of thermal fluctuations, changes in particle shape [26] or the behavior of stabilizing ligands [27,28]. It is known that the plasmonic response of systems of anisotropic nanoparticles depends strongly on the type of contacts between nanoparticles [29].…”
mentioning
confidence: 85%